Relation between kicking force and power output in taekwondo - Michalski, R.; Busko, K.; Staniak, Z.; Lach, P.; Mazur Rozycka, J.; Gajewski, J.; Gorski, M. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: Taekwondo is a combat sport where kicking techniques is essential. Punching and kicking force is rarely measured in athletes. There are few studies which describe the relation between punching force and power output or joint torque in boxers but not in taekwondo athletes. The aim of this study was to investigate the relation between maximal punching/kicking force and maximum power output measured in 10s Wingate test, maximum power output and jumping height of taekwondo athletes. Methods: The study involved six taekwondo athletes (age 17.7±0.7 years, body height 179.5±4.1 cm, weight, 62.3±6.0 kg). Measurements of maximal punching and kicking force were carried out on a boxing dynamometer. Each participant performed six punches of rear hand (3 hook and 3 straight punches) and six kicks (3 apdollyo and 3 dwit-chagi). Maximal power output and jumping height in counter movement jump (CMJ) were measured on a force plate. 10s Wingate anaerobic test (WAnT) was performed on a cycle ergometer connected to a PC. Braking force on pedals was determined by load equal to 0.075 of body weight. Statistical calculations were prepared using STATISTICA software. Results: Mean, maximal straight and hook punching forces were 1659.2±254.2 N and 1843.8±453.3 N, respectively. Maximal apdollyo right, apdollyo left and dwit-chagi kicking forces were 3541.3±1130.3 N, 3205.3±965.1 N and 3568.0 ±1306.0 N respectively. Means (±SD) of CMJ height and maximum power were 0.501±0.040 m and 2440.5±731.7 W, respectively. The maximal power output in WAnT was 704.0±66.7 W. Linear correlation coefficients were estimated between force delivered in each punching/kicking technique and the three investigated variables: power output in WAnT; power output and jumping height in CMJ. No significant correlation was found (á=0,05). Discussion: Punching force depends on the method of measurement, technical skill of athletes and punching type. The peak punching force of boxers ranged from 1990 to 4741 N in study of Waliko et al. [2005]. The values obtained in our study were smaller. Our taekwondo athletes achieved similar CMJ height (0.527±0.111 m) as those described by Noorul at al. [2008]. No relation was found between punching/kicking forces, and power output. Presented results demonstrate that no relations are between maximal punching/ kicking force, power output measured in WAnT, and jump height and power measured in CMJ in taekwondo athletes.